Resection of the primary tumour versus no resection prior to systemic therapy in patients with colon cancer and synchronous unresectable metastases (UICC stage IV): SYNCHRONOUS - a randomised controlled multicentre trial (ISRCTN30964555) - Rahbari, Nuh Nabi; Müller-Christmann, Christine; Bork, Ulrich; Stange, Annika; Jäger, Dirk; Luntz, Steffen P.; Englert, Stefan; Rossion, Inga; Koch, Moritz; Büchler, Markus W.; Kieser, Meinhard; Weitz, Jürgen (BMC cancer, 2012)
Currently, it remains unclear, if patients with colon cancer and synchronous unresectable metastases who present without severe symptoms should undergo resection of the primary tumour prior to systemic chemotherapy. Resection of the primary tumour may be associated with significant morbidity and delays the beginning of chemotherapy. However, it may prevent local symptoms and may, moreover, prolong survival as has been demonstrated in patients with metastatic renal cell carcinoma. It is the aim of the present randomised controlled trial to evaluate the efficacy of primary tumour resection prior to systemic chemotherapy to prolong survival in patients with newly diagnosed colon cancer who are not amenable to curative therapy.